2010
DOI: 10.1007/s00213-010-1915-7
|View full text |Cite
|
Sign up to set email alerts
|

A functional NOS1 promoter polymorphism interacts with adverse environment on functional and dysfunctional impulsivity

Abstract: This study provides further evidence that short alleles of NOS1 ex1f-VNTR go along with impulsive behavior. In the absence of adverse environmental conditions, this may lead to a beneficial effect as functional forms of impulsivity are affected. This however is reversed under negative conditions, as dysfunctional impulsivity is increased under these circumstances. This data provides evidence that NOS1 ex1f-VNTR is subject to balancing selection potentially explaining persistence of the risk allele in the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 20 publications
3
42
1
1
Order By: Relevance
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
“…(Donohoe et al, 2009;Nicodemus et al, 2010;Riley et al, 2010) and (Shinkai et al, 2002) only presented data on SNPs which have not been genotyped for the present study; no SNP data could be obtained from the study of (Wang et al, 2012); and the study by (Silberberg et al, 2010) was excluded because of the rather small sample size (n=26) precluding meaningful interpretation of the data. Finally, (Reif et al, 2011) and (Reif et al, 2006), were excluded because the case samples of both studies overlapped with the sample described here (while the control sample was extended more than two-fold).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted disruption of Nos1 in mice increased impulsivity and aggressiveness, reduced anxiety, and impaired learning (19,20). Human behavioral and imaging studies have shown NOS1 exon 1f-VNTR to be associated with hyperactive, impulsive, and aggressive behavior as well as hypofunctioning of the anterior cingulate cortex (15,21,22).Although the NOS1 gene has been linked to ADHD, impulsivity, and modification of neurotransmitter levels in the striatum, effects of NOS1 genetic variation on striatal activity have not been investigated. The objective of the present study was to better understand the effect of this gene on neurobiological dysfunctioning in adult ADHD by exploring the influence of the exon 1f-VNTR on impulsivity and reward-related striatal activity in a large sample of adult ADHD patients (N=87) and healthy comparison subjects (N=49).…”
mentioning
confidence: 99%
“…Nugent et al (2011) review this work with respect to the risk for developing depressive and anxiety disorders in adolescence and adulthood. Reif et al (2010) demonstrate how adaptive and maladaptive impulsivity reflect interactions of neuronal nitric oxide synthase (NOS1) genotype with adverse family environment and stressful life events in adolescents. In their epidemiological study, Elzinga et al (2010) report that brain-derived neurotrophic factor (BDNF) genotype interacts with ELS and recent life stress to lower serum BDNF levels in adults with a history of depression.…”
mentioning
confidence: 99%